Exposure to Occupational Noise: Machine Operators of Full Tree System in Brazil - Camargo, Diegoaparecido [UNESP]; Munis, Rafaelealmeida [UNESP]; Batistela, Gislainecristina [UNESP]; Simões, Danilo [UNESP] (University of Zagreb, Faculty of Forestry and Wood Technology, 2022)
Physical agent noise can be considered one of the main disturbances that compromise the occupational health of self-propelled forest machine operators. We evaluated whether occupational noise levels emitted by self-propelled forest machines employed in the full tree system are in accordance with both the National Institute for Occupational Safety and Health and ISO 1999:2013 standards, while also proposing mitigating measures aimed at protecting the operators hearing. Seventeen operators, who performed wood harvesting operations in Eucalyptus forests in Brazil, were analyzed. Noise levels were collected in a daily shift of eight hours as recommended by the Acoustics – Determination of occupational noise exposure - Engineering method for full-day measurements (ISO 9612:2009). The standards adopted for the evaluation were the exposure action value of 80 dBA and the exposure limit of 85 dBA based on the National Institute for Occupational Safety and Health – NIOSH and on Acoustics – Estimation of noise-induced hearing loss (ISO 1999:2013) Directive 2003/10/EC. The operators were arranged in homogeneous groups according to the Acoustics recommendation – Determination of occupational noise exposure – Engineering method for full-day measurements (ISO 9612:2009), classified by the operations of felling, skidding of tree bundles and bucking. The results showed that 17 self-propelled forest machines exceeded the exposure action value of 80 dBA, of which 10 machines exceeded the exposure limit of 85 dBA. It was concluded that the levels of occupational noise emitted by self-propelled forest machines used in the full tree system are higher than those recommended by both standards, National Institute for Occupational Safety and Health and ISO 1999:2013. Therefore, the allocation of selfpropelled forest machines to homogeneous groups allows inferring mitigation actions that protect operators’ hearing. The correct use of hearing protectors during the daily workday provides hearing protection for operators in mechanized wood harvesting. Adoption of actions such as maintenance of cabin seals and mechanical components, breaks for fatigue relief, reduction of daily working hours and rotation of operators in different self-propelled forest machines can mitigate the damage to the occupational health of operators.
Keywords: Ergonomics; Eucalyptus; Forest operations; Labor disorders; Physical agent; Wood harvesting